Life-Batt / Erlina Mohamad Jaaper, Puteri Najihah Megat Zakaria And Nurul Izzah Azlan - Mohamad Jaaper, Erlina; Megat Zakaria, Puteri Najihah; Azlan, Nurul Izzah (2018)
The team is developing a device called Life-Batt which enables two phones to share the battery without using a wire or external battery such as power bank. Besides, Life-Batt is also designed to be compatible with all type of phone. The idea is generated based on the observation that we did during our daily life that shows most people are facing a problem where their phones is running out of battery. Besides, we also observed that their phones could only last less than 24 hours. As we observed more into to this problem , most of people also claim that even though they have a portable charger, they sometimes forget to charge the portable charger so it is stressful for them. Different phones have different charger cable and this causing a problem to most people as they have to bring their own charger cable everywhere they go. As people nowadays preferred a convenience device to make their life is more easy, this device is suitable as it is small, wireless, and it is compatible with all type of phones so they can share it with everyone. A product concept testing with a survey conducted through our Instagram shows that 79% of our followers are interested in this device. We also conduct a survey among UiTM students by answering some questions in the google form.